2019
DOI: 10.1007/978-3-030-29729-9_2
|View full text |Cite
|
Sign up to set email alerts
|

Using Honeypots in a Decentralized Framework to Defend Against Adversarial Machine-Learning Attacks

Abstract: The market demand for online machine-learning services is increasing, and so to have are the threats to them. Adversarial inputs represent a new threat to Machine-Learningas-a-Services (MLaaSs). Meticulously crafted malicious inputs can be used to mislead and confuse the learning model, even in cases where the adversary only has access to input and output labels. As a result, there has been increased interest in defence techniques to combat these types of attacks.In this thesis, we propose a network of high-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…Apart from the normal prediction approaches which predict the potential hackers or their activities, a few researchers have devised honeypot mechanisms to protect against vulnerabilities arising out of the adversarial learning processes. Authors of [29] have suggested learning models that protect against adversarial errors opted by automated machine learning algorithms. For instance, IIoT applications, guided by machine learning services, could be exposed to wrong learning advice which could end up with hazardous results.…”
Section: Machine Learning and Explainable Aimentioning
confidence: 99%
“…Apart from the normal prediction approaches which predict the potential hackers or their activities, a few researchers have devised honeypot mechanisms to protect against vulnerabilities arising out of the adversarial learning processes. Authors of [29] have suggested learning models that protect against adversarial errors opted by automated machine learning algorithms. For instance, IIoT applications, guided by machine learning services, could be exposed to wrong learning advice which could end up with hazardous results.…”
Section: Machine Learning and Explainable Aimentioning
confidence: 99%